2021
DOI: 10.4028/www.scientific.net/ast.107.97
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water Cement Ratio on Strengths Characteristics of Concrete Produced with Recycled Iron and Steel Slag (RISS) Aggregate

Abstract: Effects of Water cement ratios on strengths characteristics of concrete produced with Recycled Iron and Steel Slag (RISS) aggregates was studied to understand the structural integrity of RISS aggregate in concrete and to determine the veracity of RISS aggregate as alternative aggregate to granite in concrete works. Mineralogical composition of the aggregate showed Silicon oxide (quartz) as the common mineral; both aggregates are well graded, strong and durable. Lower water cement ratios improved both the compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Parron-Rubio et al [11] found that when steel slag from different sources replaced 25% of the cement, the properties of concrete would change. (Raheem et al [12] studied the effect of different water-cement ratios on the strength of recycled steel slag aggregate concrete. It was found that low water-cement ratio can improve the compressive and flexural strength of concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Parron-Rubio et al [11] found that when steel slag from different sources replaced 25% of the cement, the properties of concrete would change. (Raheem et al [12] studied the effect of different water-cement ratios on the strength of recycled steel slag aggregate concrete. It was found that low water-cement ratio can improve the compressive and flexural strength of concrete.…”
Section: Introductionmentioning
confidence: 99%